De-Dollarization and South Asia: Challenges and Opportunities for Nepal in a Multipolar Currency World - Bhattarai, Keshav; Adhikari, Ambika P. (NCWA Annual Journal, 2025)
The United States dollar’s dominance as the global reserve currency, established under the 1944 Bretton Woods system, persists despite the 1971 decoupling of the gold backing to the dollar. Its liquidity, stability, and full support by the US government confer a solid financial security and advantage to the currency, including a universal acceptance of the dollar and a relatively low borrowing cost. Because of these reasons, the US dollar has been able to dominate the global financial markets for the past eight decades. However, the rapidly emerging global political and economic power shifts are challenging the status of the US dollar. In 2009, Brazil, Russia, India, China, and South Africa formed the organization BRICS as a group to work on collaboration and investment strategies. BRICS, which has now been expanded to include 10 countries, is exploring alternatives to the US dollar for international trade. The alternatives include trading with local currency and Central Bank Digital Currencies (CBDCs). Geopolitical factors, such as Western sanctions on China, Russia, Iran and other countries and China’s ambitious Belt and Road Initiative (BRI), have accelerated de-dollarization efforts as a tug of war. This tug-of-war among the powerful countries, however, has created opportunities for emerging economies to embark toward financial sovereignty and decreased dependence on the financial system that has been dominated by the West.There are mixed implications of these emerging trends for South Asia. India is pursuing rupee-based trade aspiring to enhance regional trade in Indian Rupees. Other South Asian countries also aspire to follow similar suit. There are several barriers associated with it. The limited convertibility of the currencies of the BRICS member nations makes the complete replacement of the US dollar-based international trade difficult. Nepal may face several challenges because its economy relies heavily on remittances and imports. Nonetheless, efforts in diversifying trades in regional and local currencies, leveraging CBDCs, and strengthening regional economic ties offer potential benefits in the pursuit of financial autonomy. Nepal’s strategic reforms and increased collaboration within South Asia are crucial for mitigating risks and enhancing its financial resilience in a multipolar currency system.At the global scale, de-dollarization could reduce financial risks and foster a more equitable structure, though market inefficiencies and trade barriers remain obstacles. For South Asia and Nepal, embracing financial innovation and fostering regional integration is key to navigating this transformative shift. With de-dollarization efforts leading to policy and policies, Nepal could reduce dollar dependence and enhance its role in South Asia’s evolving economic and financial matters.